DAYA HAMBAT JUS APEL MANALAGI (MALUS SYLVESTRIS) TERHADAP PERTUMBUHAN BAKTERI PORPHYROMONAS GINGIVALIS SECARA IN-VITRO - Enda Markus Aginta Sembiring; Yufri Aldi; Susi Susi (Faculty of Dentistry Universitas Andalas, 2018)
Background: Periodontitis are one of teeth and mouth disease with prevalence is 50% of adult. Periodontitis is an inflammatory condition that cause damage to connective tissue and alveolar bone. Porphyromonas ginggivalis is one of anaerob gram-negative bacteria that cause periodontitis, these bacteria can withstand host’s defenses mechanism by utilizing a virulence factor panel that cause derived innate immune and inflamatory responses. Apple Manalagi or known as apple Malang is one of the herbal plants in Indonesia. Some studies represented inhibitory effect for bacteria from its substance. Objective: The objective of this study were to determine inhibitory effect of apple manalagi (Malus sylvestris) for Porphyromonas ginggivalis. Method: Experimental laboratory. In this study Apple Manalagi will be Juiced, Juice Apple Manalagi will divide by 4 concentrate 25%, 50%, 75% and 100%. This study use diluusion method, juice apple Manalagi will aplicated to 5 samples agar MHA for 5 times. The inhibitory effect will calculated with sliding calipers, and then data will process with one way anova. Result: The result didn’t show any inhibision zone in MHA to Porphyromonas ginggivalis so data analysis cann’t be done. Conclusion: Apple Manalagi doesn’t have inhibitory effect for Porphyromonas ginggivalis.